The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1152/ajprenal.00444.2012
|View full text |Cite
|
Sign up to set email alerts
|

βENaC is required for whole cell mechanically gated currents in renal vascular smooth muscle cells

Abstract: Chung WS, Weissman JL, Farley J, Drummond HA. ␤ENaC is required for whole cell mechanically gated currents in renal vascular smooth muscle cells. Am J Physiol Renal Physiol 304: F1428 -F1437, 2013. First published April 3, 2013 doi:10.1152/ajprenal.00444.2012.-Myogenic constrictor responses in small renal arteries and afferent arterioles are suppressed in mice with reduced levels of ␤-epithelial Na ϩ channel (␤ENaC m/m ). The underlying mechanism is unclear. Decreased activity of voltage-gated calcium channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…For example, mechano-activated whole cell Na + currents have been described in vascular smooth muscle cells. 168 These currents were reduced when β subunit expression was reduced, but it is not known if these mechano-activated whole cell currents are amiloride sensitive. Vascular smooth muscle cells also express ASIC subunits, and it has been suggested that the mechano-sensory channel complexes might be composed of a combination of ENaC and ASIC subunits.…”
Section: Expression and Regulation Of Amiloride-sensitive Na+ Channelmentioning
confidence: 99%
“…For example, mechano-activated whole cell Na + currents have been described in vascular smooth muscle cells. 168 These currents were reduced when β subunit expression was reduced, but it is not known if these mechano-activated whole cell currents are amiloride sensitive. Vascular smooth muscle cells also express ASIC subunits, and it has been suggested that the mechano-sensory channel complexes might be composed of a combination of ENaC and ASIC subunits.…”
Section: Expression and Regulation Of Amiloride-sensitive Na+ Channelmentioning
confidence: 99%
“…In addition, β and γ ENaC, but not α ENaC, were identified in vascular smooth muscle cells of renal arteries, where they contribute to pressure-induced vasoconstriction (Drummond, 2007(Drummond, , 2012. Other studies provided evidence that β ENaC is essential for regulating renal arterial myogenic tone in vitro and in vivo (Chung et al, 2013). The findings in renal arteries highlight the importance of the β ENaC subunit for mechanosensation.…”
Section: Introductionmentioning
confidence: 95%
“…Since the importance of strain/stretch in activating a mammalian degenerin has not been addressed, our laboratory developed a novel in-vitro electrophysiologic assay to assess mechanically gated currents in isolated VSMCs using stretch (17). Briefly, enzymatically dissociated renal VSMCs are plated on an elasmoteric substrate coated with collagen.…”
Section: Do Degenerin Proteins Mediate Mechanically Gated Currents?mentioning
confidence: 99%